(3QSGdI aj JMbjb eG LGA Ydi hRf eaYd Ch eaYd Ch fMhgeGs - (3GdUHGf , eMeO Hf Ydj GdUHGf GdeUQj GdTGaYj GdMfaj, CHh GdYQaGf,J (B1206 (3g` s ((3CMeO cQe s)
(3ChdgG (B:s
(3hHYO, ajbhd gPg cdeGJ JJYdb HJMbjb eG LGA Ydi hR eanYd heapYd hfMhgeG eUOQkG Ch GSe ReGf Ch ecGf s
(3BNQgG (B:s
(3PcQg UGMH GdJHUQI GdKGdK(B: (3dG jYed ef GdKdGKI GdeJbOeI EdG GdeUOQ HTQhW ePchQI aj cJH GdYQHjI, hGddg SHMGfg hJYGdi CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3fSNI fbdJ ef fSNI GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B297 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B17s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B371 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B399 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B134 s
Keywords: (3GdfMhs